2014
DOI: 10.1080/13218719.2014.919643
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying: The Shades of Harm

Abstract: Empirical studies undertaken to date report that exposure to cyberbullying can have potentially serious consequences. This paper assesses the potential harm associated with the various specific manifestations (forms) of cyberbullying based on initial empirical research and a crime seriousness framework originally applied to traditional crimes. The analysis provides valuable theoretical insight into the associated harms of each of the forms of cyberbullying. This is significant in light of the infancy of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…Contrary to previous studies, which considered repetition irrelevant for cyberbullying definition (Slonje and Smith, 2008 ; Dooley et al, 2009 ; Nocentini et al, 2010 ; Compton et al, 2014 ), the present study shows that repetition affects the perceived severity of the situation when it is combined with the intention to harm (Factor 4). This combined view of the criteria, is also stressed by authors focusing on the legal implications of cyberbullying (Langos, 2015 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Contrary to previous studies, which considered repetition irrelevant for cyberbullying definition (Slonje and Smith, 2008 ; Dooley et al, 2009 ; Nocentini et al, 2010 ; Compton et al, 2014 ), the present study shows that repetition affects the perceived severity of the situation when it is combined with the intention to harm (Factor 4). This combined view of the criteria, is also stressed by authors focusing on the legal implications of cyberbullying (Langos, 2015 ).…”
Section: Discussionmentioning
confidence: 91%
“…At the moment, the statistical models cannot allow us to consider both aspects at the same time in a unique model. More attention to this aspect of different perceived severity related to different types of attacks looks very promising both from the psychological and legal points of view and needs further investigation (Nocentini et al, 2010 ; Menesini et al, 2012 ; Langos, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Langos (2013) found that emotional harm in the context of cyberbullying refers to anxiety, distress, fear, grief, anger or humiliation, and extends to more severe forms of harm, such as protracted psychological injury and long-term psychiatric harm. Considering that some types of cyberbullying are more harmful than others (Langos, 2014), its consequences can result in a continuum of effects, and therefore, attentions must focus on the severity of the incident within the context in which it occurs and the circumstances surrounding it (Hinduja & Patchin, 2010).…”
Section: From Bullying To Cyberbullyingmentioning
confidence: 99%
“…Finalmente, otra complicación que puede tener lugar en los adolescentes usuarios de Instagram es el ciberacoso, derivado del término en inglés cyberbullying, refiriéndose al uso de RRSS para acosar a una persona o grupo de personas mediante ataques personales, divulgación de información confidencial o falsa entre otros (Langos, 2015). El estudio realizado por Albdour et al (2019) obtuvo que 34% de los adolescentes reportaron victimización de ciberacoso y el 26,7% por lo menos una vez en el último año, siendo la mayoría hombres.…”
Section: Desarrollo De Trastornos En Las Emociones Y Otras Complicaciunclassified